Model Pendidikan Islam Pada Pembelajaran Bahasa Arab Perspektif Poliglot - Ahmad Zaky (ASSUNNAH PRESS, 2025)
This paper discusses language learning as practiced by polyglots. Developers of foreign language learning programs need to discuss this topic because polyglots are able to learn many languages effectively and efficiently. In terms of learning, polyglots have a different model of language learning than that used in general language learning. Polyglots have their own approaches, methods, and techniques. The focus of this paper is on classical and modern polyglots, who are the subjects of this research and will be discussed in this paper. They are individuals who master multiple languages. Classical and modern polyglots master multiple languages in different ways, which is certainly important and interesting to study. This paper is a qualitative study using content analysis methods aimed at producing an objective and systematic description of the content, as well as identifying patterns, themes, concepts, and models within it. Content analysis is used because there is sufficient digital data available on the internet to answer the questions posed in this paper. This paper will address the question of how the language learning models implemented by classical and modern polyglots are applied. The results of this paper are expected to be applied to modern foreign language learning and to produce a new learning model capable of achieving optimal foreign language learning with a model that the researcher calls media-centric.